2022
DOI: 10.1038/s41467-022-34943-w
|View full text |Cite
|
Sign up to set email alerts
|

High thermal conductivity in wafer-scale cubic silicon carbide crystals

Abstract: High thermal conductivity electronic materials are critical components for high-performance electronic and photonic devices as both active functional materials and thermal management materials. We report an isotropic high thermal conductivity exceeding 500 W m−1K−1 at room temperature in high-quality wafer-scale cubic silicon carbide (3C-SiC) crystals, which is the second highest among large crystals (only surpassed by diamond). Furthermore, the corresponding 3C-SiC thin films are found to have record-high in-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 60 publications
(113 reference statements)
1
12
0
Order By: Relevance
“…In contrast, the hydrophobic bonding results in an interlayer with varying thicknesses of 0.2–2.5 nm and an improved TBC of 100–250 MW m –2 K –1 . Meanwhile, Cheng et al grew 3C-SiC crystals on Si substrates by low-temperature CVD. They reported a record high TBC among semiconductor interfaces, which is above 600 MW m –2 K –1 .…”
Section: Tbcs Of (U)wbgs Heterostructuresmentioning
confidence: 99%
“…In contrast, the hydrophobic bonding results in an interlayer with varying thicknesses of 0.2–2.5 nm and an improved TBC of 100–250 MW m –2 K –1 . Meanwhile, Cheng et al grew 3C-SiC crystals on Si substrates by low-temperature CVD. They reported a record high TBC among semiconductor interfaces, which is above 600 MW m –2 K –1 .…”
Section: Tbcs Of (U)wbgs Heterostructuresmentioning
confidence: 99%
“…However, the aspect ratio required increases with the thermal conductivity of the solids, and therefore a much longer and thinner suspended nanostructure need to be fabricated, which is technically more challenging. In our experiment, we chose SiO 2 as a polar dielectric with a low thermal conductivity of ∼1.4 W m −1 K −1 ( cf ., Si 3 N 4 with 9 W m −1 K −1 , 43 SiC with 490 W m −1 K −1 44 and hBN with 751 W m −1 K −1 45 ). Also, importantly, amorphous SiO 2 should not exhibit size-dependent thermal conductivity for the dimensions of our samples, which are down to 100 nm owing to their short phonon mean free paths.…”
Section: Resultsmentioning
confidence: 99%
“…TDTR was an ultra‐fast laser‐based pump‐probe technique capable of assessing the thermal properties of both bulk and nanostructured materials. [ 34 ] The pump beam periodically heated the sample surface while the probe beam detected the temperature variation of the sample surface via thermoreflectance. The signal picked up by a photodetector and a Lock‐in amplifier was fitted with an analytical heat transfer solution of the sample structure to infer unknown parameters.…”
Section: Methodsmentioning
confidence: 99%
“…[ 33 ] This feature positions 3C‐SiC as an ideal solution for mitigating the challenges related to lattice mismatch during bonding processes, ultimately facilitating seamless integration of GaN and diamond materials. Furthermore, corresponding 3C‐SiC thin films have been reported to possess record‐high thermal conductivity [ 34 ] . The computation of interfacial thermal resistance by the phonon diffuse mismatch model indicated that the thermal boundary resistance for the 3C‐SiC/diamond interface is comparatively lower when compared to other diamond heterointerfaces.…”
Section: Introductionmentioning
confidence: 99%